Deconstructing service-learning : research exploring context, participation, and impacts - Billig, Shelley H.; Eyler, Janet; Furco, Andrew (Emerald Publishing Limited : Information Age Publishing, 2003)
This work looks at service learning. It cover such topics as: challenges for service-learning research; enhancing theory-based research on service learning; dilemmas of service learning teachers; the diffusion of academic service learning in teacher education; and more.
"The chapters in this volume were selected from a refereed, blind review of papers presented in October 2002 at the Second Annual K-12 International Conference on Service-Learning Research, held at Vanderbilt University in Nashville, TN"--Introd.
Keywords: Service learning -- Congresses.; elektronické knihy; Conference papers and proceedings.; Education -- Non-Formal Education.; Industrial or vocational training.; Educational systems and structures.; electronic books